2010
DOI: 10.1183/09031936.00053710
|View full text |Cite
|
Sign up to set email alerts
|

Bosentan does not improve pulmonary hypertension and lung remodeling in heart failure

Abstract: Pulmonary hypertension (PH) and right ventricular (RV) dysfunction associated with heart failure (HF) carry a poor prognosis. Although endothelin receptor antagonists (ERAs) demonstrated benefits in pulmonary arterial hypertension, their efficacy in PH associated with HF was not specifically evaluated.2 weeks after myocardial infarction (MI) rats received bosentan (100 or 200 mg?kg -1 ?day -1 ) or no treatment for 3 weeks. PH, RV hypertrophy and function as well as lung remodeling and function were evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…28 Recent work using rats with secondary PAH induced by ischemic heart failure has also shown that RV dysfunction is not improved by bosentan treatment. 29 The study by Nagendran et al 26 may partly explain why treatment with bosentan provides no significant improvement of RV dysfunction in PAH observed in those studies.…”
Section: Circulation Researchmentioning
confidence: 85%
“…28 Recent work using rats with secondary PAH induced by ischemic heart failure has also shown that RV dysfunction is not improved by bosentan treatment. 29 The study by Nagendran et al 26 may partly explain why treatment with bosentan provides no significant improvement of RV dysfunction in PAH observed in those studies.…”
Section: Circulation Researchmentioning
confidence: 85%
“…In the complex post-MI state, MCP-1 alone is unlikely to be solely responsible for lung remodelling; we have also identified elevated IL-6 levels (figure 4). Similarly, work by others has addressed other mediators, such as endothelin-1, although outcomes in both clinical trials of endothelin antagonists in HF and animal models have been negative 43 44. In addition, our modelling of the mechanical effects of PVH on the microvascular endothelium using CMS via the Flexercell system is reductionalist, but has the benefit of using HLMVECs, potential upstream targets of elevated LAP.…”
Section: Discussionmentioning
confidence: 97%
“…Plasma endothelin levels correlate with the severity of HF and with pulmonary arterial pressure and PVR, and there is direct evidence that endothelin contributes to secondary PH in the presence of left ventricular systolic dysfunction [6][7][8]. The benefits of endothelin antagonist in experimental HF have been mixed [9,10]. In some studies, they facilitated favorable hemodynamic and structural changes [9].…”
Section: Endothelin Receptor Blockersmentioning
confidence: 96%